ACSM's research methods - Armstrong, Lawrence E. 1949-; Kraemer, William J. 1953-; American College of Sports Medicine (Philadelphia Wolters Kluwer, 2016)
"Written by leading experts in the field, ACSM's Research Methods better integrates traditional methods with some of the newer approaches to research, such as qualitative and mixed methods, and uses published journal articles and real-life examples to make the material interesting and relevant."--Cover
Introduction to research methods -- The importance of research for evidence-based practice -- Choosing your research project : framing the problem, research hypotheses, and predictions -- Searching the scientific literature -- Fundamentals of study design -- Understanding research : a clinician's perspective of basic, applied, and clinical investigations -- Experimental design I -- independent variables -- Experimental design II -- dependent variables, blinding, randomization, and matching -- The unique challenges of field research -- Veracity of data : understanding validity and reliability -- Unique features in animal research -- Ethical principles in human and animal research -- Developing a funding base for your research -- Conducting a study : pilot testing, sampling, and data collection -- Instrumentation : calibration and standardization -- First analyses after data collection -- Database development and management -- Statistical approaches to data analysis -- Drawing inferences, logical fallacies -- Writing a research manuscript and determining authorship -- Submitting a manuscript for publication : finding the publication outlet -- Demands of the peer-review process -- Building the science buzz : working with media to create a lay translation of your discovery.
Includes bibliographical references and index.
Keywords: Sports medicine -- Research -- Methodology; Research design; Sports Medicine; Exercise; Physical Fitness